Associations between prenatal phthalate exposure and maternal immune cell profiles across trimesters - Yi Zhang; Lin Tao (Frontiers in Public Health, 2026)
Introduction Phthalates (PAEs) are endocrine-disrupting chemicals, yet the association between prenatal PAE exposure and maternal blood immune cells remains unclear. Here, we enrolled 2,581 pregnant women, including 287 in the first trimester (gestational weeks 1–12), 807 in the second trimester (gestational weeks 13–27), and 1,487 in the third trimester (gestational weeks 28 to delivery). This study aimed to elucidate the association between urinary phthalates (PAEs) metabolites during pregnancy and characteristics of the maternal immune cell profile. Methods First, we analyzed differences in maternal PAE metabolites and immune cell counts (leukocytes, lymphocytes, neutrophils, eosinophils, basophils, monocytes, and platelets) in the three gestational stages using non-parametric alternatives (Kruskal-Wallis test). Subsequently, linear regression models quantified correlations between PAE metabolites and immune cell counts, while restricted cubic spline (RCS) analysis explored dose–response relationships between the two. Finally, Bayesian kernel machine regression (BKMR) was used to assess the non-linear associated between PAE metabolites and immune cells. Results Findings revealed pregnancy-stage differences in both maternal PAE metabolites and maternal immune cell counts within each trimester. Linear regression identified significant associations between specific PAE metabolites and immune cell subsets, while RCS models further confirmed dose–response relationships for multiple metabolites. BKMR analysis highlighted a nonlinear association between combined exposure to PAE metabolites and basophils, monocytes, and lymphocytes. Discussion In summary, this study has preliminarily established an association between prenatal maternal exposure to PAE metabolites and immune cells in maternal blood, highlighting the potential immunomodulatory effects of PAE exposure during pregnancy. However, as this study is primarily based on epidemiological research, all findings should be interpreted with caution.